Efektivitas Pembelajaran Bahasa Arab di Madrasah Ibtidaiyyah Melalui Pendekatan Inovatif - Azizah (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2025)
Learning Arabic at the Madrasah Ibtidaiyyah level often faces challenges in terms of student engagement and achieving optimal learning outcomes. Considering the importance of mastering Arabic as a language of religion and communication in the context of Islamic education, efforts are needed to increase the effectiveness of learning through the application of innovative approaches. This research aims to explore and analyze the effectiveness of implementing innovative approaches in Arabic language learning at Madrasah Ibtidaiyyah. This research using qualitative research methods through library research. The data was obtained through the exploration and analysis of various relevant literature sources, including books, journal articles, and other academic publications. Various relevant literature sources were identified and analyzed to understand the impact of using innovative approaches, such as digital technology, project-based learning, and gamification, on improving students' language skills. The results of the study show that these approaches not only improve students' language skills, but also motivate them to be more active and participate in the learning process. This innovative approach is proven to be able to create a more interactive and contextual learning environment, which ultimately improves students' overall understanding and Arabic language skills. Thus, this research concludes that the implementation of an innovative approach in learning Arabic at Madrasah Ibtidaiyyah has a significant positive impact on learning effectiveness.